Online Stock Trading Workshop In Providing Understanding To The Public To Invest The Indonesia Stock Exchange - Amena Allouch (International Journal of Community Service Implementation, 2023)
Investment is defined as the process of capital investment undertaken by an investor both foreign and domestic investors with the aim of making a profit. Investment is a term that is familiar to the public, both the upper, middle and lower class. However, most people have the perception that being an investor must be people who have a lot of money, especially for investing in large companies that are well known. Actually, this perception can be minimized by inviting people to conduct online trading training and providing an understanding to them that being an investor is not only among people who have a lot of money. Currently, the Indonesia Stock Exchange has made it easy for investors from the lower middle class to be able to act as investors. The solution provided by the Indonesia Stock Exchange is to reduce the number of shares in 1 lot, which is 100 shares. Finally, it is expected that with this online trading training activity, it can attract people to invest in the capital market.